Produção otimizada de substâncias antimicrobianas, a partir de biossíntese dirigida, por Aspergillus parasiticus e síntese de derivados clovânicos ativos contra o fitopatógeno Botrytis cinerea - Adriana de Almeida Pinto Bracarense (2013)
The fungus Aspergillus parasiticus is known for producing aflatoxins, secondary metabolites toxic to animals and to humans. Despite producing toxic metabolites to human health, important metabolites with anticancer (sequoiamonascins A-D), antimicrobial and skin lightening activities (kojic acid) have been isolated from this species. The first part of this study aimed to determine the optimal operating conditions for the production of kojic acid, to promote metabolic diversification, as well as to modulate the biosynthesis of antimicrobial metabolites from the fungus A. parasiticus. This fungus was cultivated in 120 different conditions. For the evaluation of operational parameters analysis of variance was used, with factorial planning 2² and 2³. The variables studied were the culture medium, agitation, carbohydrate type and carbohydrate concentration and, in response, the number of peaks obtained by HPLC-DAD has been monitored. To evaluate antimicrobial activity, the following strains from Biotechnology and Bioassays Laboratory (LABB) collection were used: Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli (bacteria), Candida albicans (yeast) and A. flavus (filamentous fungus). Four optimum conditions were established for production of kojic acid, seven conditions for metabolic diversification and thirteen conditions led to the modulation of antimicrobial metabolites production.Among the culture medium evaluated, is possible to highlight the medium LCS150 that, in the absence of agitation and with 12 days of fermentation, provided the best yield of kojic acid (65.4%) from crude extract; the culture medium YES, in the absence of agitation and with 27 days of fermentation, provided 21 metabolites as detected by HPLC-DAD; the culture medium LCG20, in the absence of agitation and after 15 days of cultivation, proved to be the most suitable condition for the production of metabolites active against E. coli (69.8 ± 1.1% inhibition). The thirteen growing conditions found for modulation of antimicrobial metabolites provided extracts that showed biological activity with IC40 for at least one of the microorganisms tested. The second part of this work involved the Botrytis cinerea fungus, responsible for the condition called "grey rot", known to cause great economic losses in crops of vegetables and fruits. Its great ability to adapt to extreme conditions, along with the resistance presented to various fungicides make B. cinerea a fungi feared by farmers. This part of the work aimed to employ the methodology of fungicides biosynthetic design, in order to prepare specific derivatives for the combat of this phytopathogen. Fifteen substances were synthesized having clovane skeleton (four ariloxyclovane, six clovanophenylamine, a clovaneaminopyrimidin, three clovanephenylamidine and one clovanebenzamide) and three with cariolane skeleton, from caryophyllene oxide. Among the substances prepared, fifteen are novel. All substances prepared were tested against the fungus B. cinerea. Of these, only two have not been active in the concentration evaluated (250 ìg L-1), demonstrating the efficiency of the methodology employed. All clovanephenylamine presented more than 90% inhibition. In order to evaluate the specificity of inhibition against this phytopathogenic fungus, antifungal assays were conducted with Penicillium crustosum. The compounds prepared were less active against this fungus, confirming a specific inhibition mechanism against B. cinerea.